An Investigation of the Allelopathic Properties of Various Weed Species in the Eastern Denpasar Region of Bali - Andriani, AASPR; Ni Luh Putu Putri, Setianingsih; Nazir, N; Dewi, W S; Indrayatie, E. R.; Kalimutu, P.K. (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Weeds are plants that live wild on cultivated land, which can reduce the productivity of cultivated plants. Phytochemical content in weeds has various benefits besides food, such as vegetable pesticides, pharmaceuticals, industry, and cosmetics. For this reason, this research aims to analyze the content of secondary metabolite compounds and measure the levels of allelopathic phytochemical compounds in several weed plants. Various substances have been identified in the form of allelopathy, namely flavonoids, tannins, phenolic acids, ferulic acid, coumarins, terpenoids, steroids, cyanohydrins, quinones, cinnamic acid, and their derivatives. Compounds identified as allelochemical compounds are flavonoids, tannins, phenolic acids, ferulic acid, coumarins, steroids, terpenoids, cinnamic acids, and their derivatives. Exploratory methods to identify plant types, experimental methods with phytochemical screening tests to characterize types of secondary metabolite compounds, and allelopathic toxicity tests Based on the results and discussion that have been presented, it can be concluded that the weeds Echinochloa crus-galli, Panikum repen, Euphorbia hirta, Ageratum conyzoides, and Imperata cindrica contain flavonoid, tannin, and phenol compounds. The weeds with the highest scores in the phytochemical test are Echinochloa crusgalli and Ageratum conyzoides.